Between military rule and democracy: Regime consolidation in Greece, Turkey, and beyond - Gürsoy, Y. (University of Michigan Press, 2017)
Why do the armed forces variously intervene in politics via short-lived coups d’état, establish or support longer-term authoritarian regimes, or come under the democratic control of civilians? To find answers, Yaprak Gürsoy examines four episodes of authoritarianism, six periods of democracy, and ten short-lived coups with various degrees of success in Greece and Turkey and then applies the resultant theory to four military interventions occurring more recently in Thailand and Egypt. In an afterword, she addresses the July 2016 coup attempt in Turkey. Basing her findings on more than 150 interviews with Greek and Turkish elites, Gürsoy offers a detailed analysis of both countries from the interwar period to the recent regime crises. She brings together the literatures on regime change and civil-military relations by amending Robert Dahl’s framework of costs of toleration and suppression. She argues that officers, politicians, and businesspeople prefer democracy, authoritarianism, or short-lived coups depending on their perception of the degree to which their interests are threatened by each other and the lower classes. The power of the elites relative to the opposition, determined partly by the coalitions they establish with each other, affects the success of military interventions and the consolidation of regimes. With its historical and theoretical depth, Between Military Rule and Democracy will interest students of regime change and civil-military relations in Greece, Turkey, Thailand, Egypt, and other countries facing similar challenges to democratization. © 2017 by Yaprak Gürsoy. All rights reserved.